DAMPAK PERUBAHAN IKLIM TERHADAP USAHA APEL DI KECAMATAN PONCOKUSUMO KABUPATEN MALANG - Juli Rahaju; Muhandoyo Muhandoyo (Fakultas Pertanian Universitas Yudharta Pasuruan, 2017)
Climate change has a significant imp act in the fields of agricultur e , b ecause agriculture has a heavy reliance on climate elements . Therefore , studies on the impa ct of climate change on agriculture is important to study . This case study was conducted in Poncokusumo , Malang Regency for 7 months . Subjects were apple growers who have made apple cultivation for 10 years or more and still trying to apple today . Th e research object is climate change with the elements that will be Studied include temperature, humidity and rainfall and Adaptation Efforts that have been done the farmer . The results Showed that both climatic elements of temperature, humidity and rainf all simultaneously Contribute Significantly to the productivity of the apple . Separately rainfall only significant role . Respondents who did the adaptation as much as 85.29 % of the total respondents . Form of adaptation by farmers are watering the plant s to cope with high temperatures , intercropping to address the decline in income from apples , the reduction of more branches to cope with the humidity and spraying pesticides more intensively to address the incidence of diseases by the caused by rainfall and high humidity .